Time-effect relationship between spare-time exercise and sleep quality in middle school student by parallel latent growth and cross-lagged panel model - Wei, Ziming; Sha, Mo; Bu, Zixia; Liu, Yujie; Gao, Yue; Dong, Fuqiang; Jiang, Shan; Huang, Da (Frontiers in Psychology, 2025)
IntroductionSleep quality (SQ) is an important factor affecting the life and academic performance of secondary school students, and it has been found that spare-time exercise (STE) can improve SQ, but the psychological mechanism and timeliness have not been elucidated. Therefore, this study analyzed it using cross-lagged panel model (CLPM) and parallel latent growth modeling (PLGM).MethodsA total of 894 students from six secondary schools in Beijing, China, participated in the study. Participants were monitored over time through three 4-month intervals (T1, T2, T3) using the International Physical Activity Questionnaire (IPAQ) and the Pittsburgh Sleep Quality Index (PSQI). Data analysis was conducted using Pearson's test, CLPM, and PLGM.ResultsCorrelation results showed a significant negative correlation between STE and SQ across the 3 measures (r = [−0.31, −0.14]; P < 0.01). PSQI results showed a linear decreasing trend in STE (slope = −0.04, P < 0.01) and a linear increasing trend in SQ (slope = 0.02, P < 0.01) among secondary school students across the 3 time periods. CLPM results showed that the initial level of STE negatively predicted the initial level and subsequent growth rate of SQ (β = −0.20, P < 0.01). The decreasing rate of STE significantly predicted the later SQ growth rate β = −0.06, P < 0.01). (4) STE was a negative predictor of SQ (β = −0.17, P < 0.01).Conclusion(1) Initial levels of STE in secondary school students negatively predicted the rate of development of SQ over the course of the study, and higher levels of STE may have been a protective factor in the development of SQ levels. (2) The effect of STE on SQ was more stable, negatively predicting SQ at the next time point for all three measurements. SQ, on the other hand, had no significant effect on changes in STE. (3) STE decreases over time, so continued exercise and intensity are key to improving SQ.